PENERAPAN NILAI-NILAI PANCASILA DALAM MENCEGAH PERILAKU BULLYING DAN CYBERBULLYING DI ERA DIGITAL - Amanda Nur Indah; Muhammad Fatih; Shafira Ramadhani; Zaenul Slam (Universitas Nias Raya, 2025)
The phenomena of Bullying and cyberbullying have become significant social issues, threatening human dignity and social harmony, especially in the digital era. The anonymity provided by digital platforms exacerbates these problems, necessitating comprehensive prevention strategies. This study explores how Pancasila, the foundational ideology of Indonesia, can guide efforts to combat online aggression. Using qualitative literature review and thematic analysis, five key principles of Pancasila are identified as relevant: the First Principle promotes spiritual awareness; the Second emphasizes individual dignity as a moral compass; the Third advocates tolerance to combat discrimination; the Fourth encourages resolution of online conflicts through deliberation; and the Fifth underpins social justice. These principles collectively offer a philosophical framework for fostering ethical and civilized digital citizens. Integrating Pancasila into digital behavior strategies can strengthen efforts to address cyberbullying, ensuring respect, tolerance, and justice in the digital space, which is crucial in today’s interconnected world.